Variation of Oriental Oak (Quercus variabilis) Leaf δ13C across Temperate and Subtropical China: Spatial Patterns and Sensitivity to Precipitation - Du, Baoming; Kang, Hongzhang; Zhu, Yanhua; Zhao, Xuan; Yin, Shan; Burgess, Paul J.; Liu, Chunjiang (MDPI, 2015)
The concentration of the carbon-13 isotope (leaf δ13C) in leaves is negatively correlated with the mean annual precipitation (MAP) atlarge geographical scales. In this paper, we explain the spatial pattern of leaf δ13C variation for deciduous oriental oak (Quercus variabilis Bl.) across temperate and subtropical biomes and its sensitivity to climate factors such as MAP. There was a 6‰ variation in the leaf δ13C values of oak with a significant positive correlation with latitude and negative correlations with the mean annual temperature (MAT) and MAP. There was no correlation between leaf δ13C and altitude or longitude. Stepwise multiple regression analyses showed that leaf δ13C decreased 0.3‰ per 100 mm increase in MAP. MAP alone could account for 68% of the observed variation in leaf δ13C. These results can be used to improve predictions for plant responses to climate change and particularly lower rainfall.
Keywords: Carbon isotope; Oak; Precipitation; Latitude; Quercus variabilis